Indução de resistência por rizobactérias como mecanismo de controle biológico de doenças do arroz - Schafer, Jaqueline Tavares (2011)
The rice crop is subject to the occurrence of various diseases that cause yield losses of crops. Currently is seeking alternative ways to control these diseases, and biocontrol a viable possibility. The aim of this study was to compare the control of brown spot and leaf scald of rice provided by rhizobacteria isolated and combined, their impact on grain production, as well as the involvement of induced resistance associated with the activity of catalases and peroxidases. We used the DFs185 rhizobacteria (Pseudomonas synxantha) DFs223 (P. fluorescens), DFs306 (not identified), and DFs416 DFs418 (Bacillus sp.). And some combinations of these. Rice seeds of El Paso 144L were immersed in suspensions (A540 = 0.5) for each of the bacterial treatments and agitated for 30'/10°C. Seeds immersed in saline and saline plus fungicide were used as control. The experiment was conducted in a greenhouse, with assessment of disease severity in two separate trials. The first was conducted by the production and second, plants were collected at three different times to check the enzyme activity (0 h before inoculation, 24 and 168 h after). The experimental design was completely randomized. In general, the bacterial treatments were able to control both diseases, except DFs306 not provided effective control of brown spot in the first trial. In plants inoculated with Bipolaris oryzae, no treatment was able to increase production of grains or grains with lower intensity of staining. Already in plants inoculated with Gerlachia oryzae, all treatments resulted in increase of at least one variable related to production. In general, it was possible to associate the participation of enzymes evaluated the control provided by some treatments. Thus, it is believed that the bacterial treatments, individual and combined, have the potential to control brown spot and leaf scald and ability to induce resistance by altering the activity of catalases and peroxidases.